2010
DOI: 10.1016/j.jmmm.2010.02.048
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and electrical properties of RCo2Mn (R=Ho, Er) compounds

Abstract: The RCo2Mn (R= Ho and Er) alloys, crystallizing in the cubic MgCu2-type structure, are isostructural to RCo2 compounds. The excess Mn occupies both the R and the Co atomic positions. Magnetic, electrical and heat capacity measurements have been done in these comounds. The Curie temperature is found to be 248 K and 222 K for HoCo2Mn and ErCo2Mn respectively, which are considerably higher than that of the corresponding RCo2 compounds. Saturation magnetization values calculated in these samples are less compared … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…The cubic Laves phases RT 2 (R = rare earth, T = transition metal) series magnetic materials were studied intensively because of their unique electronic and magnetic structures, which lead to many physical properties such as giant magnetocaloric effect, magnetoresisitance [1,2], and hydrogen storage capacity [3]. Typical Laves phases include the cubic C 15 (MgCu 2 ), hexagonal C 14 (MgZn 2 ), and hexagonal C 36 (MgNi 2 ) [3].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The cubic Laves phases RT 2 (R = rare earth, T = transition metal) series magnetic materials were studied intensively because of their unique electronic and magnetic structures, which lead to many physical properties such as giant magnetocaloric effect, magnetoresisitance [1,2], and hydrogen storage capacity [3]. Typical Laves phases include the cubic C 15 (MgCu 2 ), hexagonal C 14 (MgZn 2 ), and hexagonal C 36 (MgNi 2 ) [3].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [5,6] discovered RNi 2 Mn (R = Tb, Dy, Ho, Er) compounds, which crystallize in the cubic MgCu 2 -type structure (F d3 m, space group). Recently, it was reported that RCo 2 Mn with R = Ho and Er also crystallize in the cubic MgCu 2 -type structure [2]. It was found that the introduction of Mn into RT 2 (T is 3d or 4d transition metal) compounds led to a significant modification of magnetic properties such as the Curie temperature [2,4,[7][8][9][10][11], magnetic entropy change [4], saturation moment [2], the nature of the magnetic transition [4], and so on.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Such differences in the space group for TbNi 2 Mn indicate that the structural and magnetic properties of RNi 2 Mn compounds may be ultra sensitive to sample synthesis and heat-treatment conditions, 1-4 similar to the case in RNi 2 systems. 5 Quite recently, Maji et al 6 reported that the RCo 2 Mn (R ¼ Ho and Er) alloys also crystallize in the cubic MgCu 2type. Moreover, many attempts have been made to use experimental and theoretical atomic parameters to construct structural maps for various MgCu 2 -type (Fd-3m space group) compounds owing to their relatively simple crystal structure and outstanding magnetic properties.…”
mentioning
confidence: 99%